Antidiabetic, Antihypertensive and Statin Medication Use in Metabolic Syndrome - Ie Butkowski E; Brix L; Al-Aubaidy HA; Kiat H; Jelinek HF (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2016)
Background: Metabolic syndrome (MetS) is characterised by a cluster of metabolic risk factors, which eventually increases the risk of diabetes and cardiovascular disease (CVD). The aim of the current study was to investigate medication use in outpatient communities with respect to the occurrence of these metabolic risk factors as defined by ATPIII. Methods: Data for this study was obtained from patients attending a diabetes health screening clinic (DiabHealth) in south-eastern Australia between 2005 and 2011. Participants had a medical history taken and anthropomorphic data collected. Participants with three or more MetS factors were classified as MetS positive as outlined by the National Cholesterol Education Program Adult Treatment Panel III (ATP III). Results: Antidiabetic, antihypertensive and antihyperlipidaemic use varies significantly in uptake by participants and with respect to the number of ATPIII factors present. Blood glucose levels (BGL) and the female waist circumference were significantly better in the MetS compared to the non-MetS group. The most increase in medication use in the MetS group was seen for antidiabetic medication (21.3% versus 2.4%, p < 0.01) compared to the non-MetS group. Antihypertensive use tripled (67.8% vs. 26.03%) and Statin use doubled significantly (p<0.01) in the MetS group (21.8% vs. 8.9%). Conclusion: Medication use increases with an increase in ATPIII factors present in the study. Participants with increased BGL (>6.1mmol/L) were not found to have antihyperglycemic medication prescribed. However both antihypertensive medication and Statins were extensively prescribed in cases where only 1 and 2 ATP factors for MetS were present.